Influence of Contact System Deficiencies during Cardiopulmonary Bypass - Agostini, Angelo; Cugno, Massimo (Thrombosis and Haemostasis, 2001)
As a result of the expanding indications for cardiopulmonary bypass (CPB) there is a growing number of patients undergoing this procedure who are at high surgical risk, and increasing efforts to investigate the mechanisms involved in CPB complications are warranted. Blood contact with foreign surfaces triggers systemic inflammatory response and may induce coagulation (1), this is believed to be responsible of most of the unwanted effects associated with CPB. During this procedure, contact phase activation occurs (2), involving factor XII (FXII), prekallikrein (PK) and high molecular weight kininogen (HK). FXII binds to negatively charged surfaces undergoing autoactivation with cleavage of Arg353-Val354 to form a two-chain molecule of 80 kD, i.e. activated FXII (FXIIa, also known as FXIIa). FXIIa can cleave PK to kallikrein which in turn cleaves FXII to produce FXIIa and a factor XII fragment of 28-30 kD (FXIIf, also known as FXIIa) and cleaves HK to HKa generating the nonapeptide bradykinin. FXIIa can cleave both FXI and PK to active enzymes, while FXIIf (which cannot bind to surfaces) cleaves PK (2) and the first component of complement (C1) (3). These mechanisms of activation differ from those initiating the coagulation cascade during in vivo haemostasis through the tissue factor pathway as a result of tissue injury (4).